IMPLEMENTASI PENDIDIKAN KARAKTER DISPILIN BELAJAR SISWA KELAS IV DI SDN 001 TAMBUSAI KABUPATEN ROKAN HULU - Selvy Syahmiati; Laili Rahmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of character education in fostering learning discipline among fourth-grade students at SDN 001 Tambusai, Rokan Hulu Regency. The research employed a qualitative approach with a case study design. The participants consisted of the principal, fourth-grade teachers, and students. Data were collected through observations, in-depth interviews, and documentation, while data validity was ensured through source, technique, and time triangulation. The data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that the implementation of learning discipline character education has been carried out effectively through classroom learning activities, habituation, role modeling, and positive reinforcement provided by teachers and the school. Students generally demonstrated disciplined behavior by attending school on time, paying attention during lessons, completing assignments, complying with school regulations, managing their learning activities at home, and preparing learning materials before attending school. Teachers played a strategic role as role models, facilitators, motivators, and supervisors in cultivating students' disciplinary values. Although several students still required continuous guidance and parental support, the implementation of character education contributed positively to improving students' responsibility, independence, compliance with school rules, and overall learning discipline. These findings highlight the importance of collaboration between schools and families in strengthening students' character development.